An unusual cause of atrial fibrillation in a young active duty soldier - Rafik BenAbda, DO; Anne Gunn, DO; Eric Roberge, MD; Ting-Wei Yang, MD (Radiology Case Reports, 2017)
Coronary artery fistula (CAF) is an abnormality in which the coronary artery has an anomalous connection with a venous structure such as the coronary sinus or atrium. CAF is usually congenital, but may be acquired. The prevalence in the general population is low with many asymptomatic and discovered incidentally. When symptomatic, CAF may present with dyspnea, decreasing functional capacity, and/or arrhythmia. We report a case of a young otherwise healthy active duty male with progressive symptoms of dizziness and exertional fatigue with paroxysmal atrial fibrillation. An electrically negative, but symptomatically positive stress test led to further workup with coronary computed tomography angiogram, which unexpectedly revealed large coronary fistulas between the aneurysmal right coronary artery and coronary sinus and the dilated left circumflex artery with probable collateralization to the coronary sinus. Cardiac magnetic resonance imaging and cardiac catheterization supported these findings and demonstrated no evidence of significant shunting.